The evidence base for interventions delivered to children in primary care: an overview of cochrane systematic reviews. - Peter J Gill; Kay Yee Wang; David Mant; Lisa Hartling; Carl Heneghan; Rafael Perera; Terry Klassen; Anthony Harnden (PLoS ONE)
Background As a first step in developing a framework to evaluate and improve the quality of care of children in primary care there is a need to identify the evidence base underpinning interventions relevant to child health. Our objective was to identify all Cochrane systematic reviews relevant to the management of childhood conditions in primary care and to assess the extent to which Cochrane reviews reflect the burden of childhood illness presenting in primary care. Methodology/principal findings We used the Cochrane Child Health Field register of child-relevant systematic reviews to complete an overview of Cochrane reviews related to the management of children in primary care. We compared the proportion of systematic reviews with the proportion of consultations in Australia, US, Dutch and UK general practice in children. We identified 396 relevant systematic reviews; 358 included primary studies on children while 251 undertook a meta-analysis. Most reviews (n = 218, 55%) focused on chronic conditions and over half (n = 216, 57%) evaluated drug interventions. Since 2000, the percentage of pediatric primary care relevant reviews only increased by 2% (7% to 9%) compared to 18% (10% to 28%) in all child relevant reviews. Almost a quarter of reviews (n = 78, 23%) were published on asthma treatments which only account for 3-5% of consultations. Conversely, 15-23% of consultations are due to skin conditions yet they represent only 7% (n = 23) of reviews. Conclusions/significance Although Cochrane systematic reviews focus on clinical trials and do not provide a comprehensive picture of the evidence base underpinning the management of children in primary care, the mismatch between the focus of the published research and the focus of clinical activity is striking. Clinical trials are an important component of the evidence base and the lack of trial evidence to demonstrate intervention effectiveness in substantial areas of primary care for children should be addressed.